Mapeamento das competências gerenciais dos sevidores técnico-administrativos do sistema de bibliotecas da universidade federal da Paraíba - Santos , Joás Jerônimo dos (2017)
The present research has as main objective the mapping of the managerial competences of the Technical-Administrative occupants of the positions of director, leadership and coordination of the System of Libraries - SISTEMOTECA - of the Federal University of Paraíba, aiming at the strengthening of the Management by Competences in the institution; And the specific objectives: a) To characterize the People Management Policy of the UFPB, particularly the Management by Competencies; B) To know the legal frameworks of Management by Competencies in the Federal Public Administration and in the UFPB; C) To identify the managerial competencies of the Technical-Administrative servers of the UFPB; And d) Proposing suggestions for measures to strengthen Management by Competencies within the UFPB. The theoretical basis was structured in six parts: i) People Management in the Federal Public Administration; Ii) The Management of People in the UFPB; Iii) Management by Competence; (Iv) skills; V) Management competences; And vi) Dimensions of Competencies. The screen survey can be classified as applied, exploratory, descriptive and documentary, with a qualitative and quantitative approach. Semi-structured interviews and questionnaires were considered as a source of data collection. The research scenario was composed by the Central Library and Sectoral Libraries of the UFPB. In the data collection, which covered 8 managers of the Library System, interviews were conducted with the objective of revealing the managers' perceptions and identifying the managerial skills already developed by them. The interviews were recorded in an electronic device and transcribed through the Content Analysis (Categories) of Bardin (1997). Subsequently, a survey was carried out with 18 managers of SISTEMOTECA. The results allowed to expand the apprehension about the managerial competences of the managers of the Library System of the Federal University of Paraíba, identifying 19 managerial competencies categorized in four dimensions: Functional Managerial Competencies, Political Managerial Competencies, Behavioral Management Competencies and Cognitive Management Competencies. There were also certain levels of mastery and encouragement of competencies, according to managers' perceptions. The present work can be an instrument for reviving the People Management of the UFPB and provoking a debate about the encouragement of the application of managers' competences. By aligning the managerial skills of the administrative staff of the Library System with the institution's objectives, the organization can expand the scope of its competencies. Moreover, the present study sought to contribute to the deepening of managerial competences within the scope of the Library System, strengthening the Management by Competences as a technology of people management at the Federal University of Paraíba.